Comparison of Groundwater Storage Changes From GRACE Satellites With Monitoring and Modeling of Major U.S. Aquifers. Issue 12 (24th November 2020) - Rateb, Ashraf; Scanlon, Bridget R.; Pool, Donald R.; Sun, Alexander; Zhang, Zizhan; Chen, Jianli; Clark, Brian; Faunt, Claudia C.; Haugh, Connor J.; Hill, Mary; Hobza, Christopher; McGuire, Virginia L.; et al.
Abstract: GRACE satellite data are widely used to estimate groundwater storage (GWS) changes in aquifers globally; however, comparisons with GW monitoring and modeling data are limited. Here we compared GWS changes from GRACE over 15 yr (2002–2017) in 14 major U.S. aquifers with groundwater‐level (GWL) monitoring data in ~23, 000 wells and with regional and global hydrologic and land surface models. Results show declining GWS trends from GRACE data in the six southwestern and south‐central U.S. aquifers, totaling −90 km 3 over 15 yr, related to long‐term (5–15 yr) droughts, and exceeding Lake Mead volume by ~2.5×. GWS trends in most remaining aquifers were stable or slightly rising. GRACE‐derived GWS changes agree with GWL monitoring data in most aquifers (correlation coefficients, R  = 0.52–0.95), showing that GRACE satellites capture groundwater (GW) dynamics. Regional GW models (eight models) generally show similar or greater GWS trends than those from GRACE. Large discrepancies in the Mississippi Embayment aquifer, with modeled GWS decline approximately four times that of GRACE, may reflect uncertainties in model storage parameters, stream capture, pumpage, and/or recharge rates. Global hydrologic models (2003–2014), which include GW pumping, generally overestimate GRACE GWS depletion (total: approximately −172 to −186 km 3 ) in heavily exploited aquifers in southwestern and south‐central U.S. by ~2.4× (GRACE: −74 km 3 ), underscoring needed modeling improvements relative to anthropogenic impacts. Global land surface models tend to track GRACE GWS dynamics better than global hydrologic models. Intercomparing remote sensing, monitoring, and modeling data underscores the importance of considering all data sources to constrain GWS uncertainties. Plain Language Summary: The major U.S. aquifers provide an ideal system to assess GRACE (Gravity Recovery and Climate Experiment) satellite data. We compared GRACE groundwater storage anomalies (GWSAs) with groundwater level anomalies (GWLAs) from ~23, 000 wells and with groundwater storage (GWS) from regional and global models in 14 major U.S. aquifers. Results show large GWS declines from GRACE in southwestern (Central Valley and Arizona Alluvial Basins) and south‐central (Central and Southern High Plains and Texas) aquifers from multiyear droughts (5–15 yr). In contrast, GWS trends in aquifers throughout the rest of the U.S. showed mostly stable or rising values. Time series of GRACE GWSAs compared favorably with GWLAs from most aquifers, suggesting that GRACE data track groundwater (GW) dynamics. Regional GW models show similar or greater declines in GWS compared with GRACE data, with the largest discrepancy of a factor of four times greater modeled depletion in the Mississippi Embayment. Global hydrologic models show minimal storage dynamics but greatly overestimated GWS declines by ~2.4× in southwestern and south‐central aquifers with intensive irrigation compared with GRACE data. In contrast, global land surface models show similar GW dynamics to GRACE data but underestimated GWS declines in heavily exploited aquifers because these land surface models do not include human intervention. Key Points: GRACE satellites track GW storage in U.S. aquifers based on good agreement between GRACE and in situ GW level monitoring (23, 000 wells) Regional models capture GRACE GW storage in most aquifers, except the Mississippi Embayment, which overestimates GRACE GWS trends by approximately four times Global hydrologic models overestimate GW depletion compared with GRACE by ~2.4× in heavily depleted aquifers in the SW and SC United States